Henriet Benoît (2021) - Colonial Impotence: Virtue and Violence in a Congolese Concession (1911-1940) - Bernault, Florence (Revue d’histoire contemporaine de l’Afrique, 2024)
Recensé : Benoît Henriet, Colonial Impotence: Virtue and Violence in a Congolese Concession (1911-1940), Berlin, De Gruyter, 2021, XIV + 191 p.